2014
DOI: 10.3329/sja.v11i1.18371
|View full text |Cite
|
Sign up to set email alerts
|

Integrated nutrient management on weed dynamics of cotton based cropping systems in South India

Abstract: Field experiments were conducted at the farm of Tamil Nadu Agricultural University, Coimbatore, India during 2007 and 2008 to assess the weed population, dry matter production, weed smothering efficiency and yield of seed cotton in a cotton based cropping system with conjunctive use of NPK and bioinoculants. Cotton intercropped with Sesbania along with application of Azospirillum and Pseudomonas recorded the lowest weed population and weed dry matter production. The maximum weed suppression of 54.5 and 44% was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This was probably due to greater temporal and spatial complementarity. The results are in agreement with the findings of [25], who observed that combined application of 100% recommended dose of NPK and bio-inoculants recorded the maximum CEY of 2,460 and 2,190 kg per hectare in 2007 and 2008, respectively. CEY differed significantly due to INM treatments (Table 3).…”
Section: Effect Of Inm On Resource Use Efficiency Of Intercropping Sysupporting
confidence: 92%
“…This was probably due to greater temporal and spatial complementarity. The results are in agreement with the findings of [25], who observed that combined application of 100% recommended dose of NPK and bio-inoculants recorded the maximum CEY of 2,460 and 2,190 kg per hectare in 2007 and 2008, respectively. CEY differed significantly due to INM treatments (Table 3).…”
Section: Effect Of Inm On Resource Use Efficiency Of Intercropping Sysupporting
confidence: 92%
“…The cotton crop (Gossypium hirsutum L.) is a species of great importance for the agricultural sector in the world, as highlights the works of Khalafalla & Abdellatef (2008), Almeida et al (2010), Silva et al (2012), Naim et al (2013), Marimuthu & Subbian (2013) and Nazir et al (2014) and, together with the species Gossypium barbadanse L., make up 98% of world production according to Azmat & Khan (2010).…”
Section: Introductionmentioning
confidence: 99%